PROPERTY LAW IN MODERN ECONOMIC TRANSACTIONS: A LITERATURE REVIEW OF OWNERSHIP RIGHTS, PLEDGES, AND MORTGAGES ON MOVABLE AND IMMOVABLE PROPERTY - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Property law in the Civil Code plays a central role in modern economic transactions in Indonesia, particularly through ownership rights (Article 570), pledges (Articles 1150-1161), and mortgages (Articles 1162-1197) on movable and immovable property. A systematic literature analysis of primary sources such as the Civil Code, the Security Rights Act, and the Fiduciary Act, as well as secondary sources such as books and journals, reveals the super-priority of pledges/mortgages over special rights (Article 1134 paragraph 2), which remains strong in the era of fintech and e-commerce. Successful adaptations include Pegadaian's digital pawn, fractional NFT mortgages, and EV leasing fiduciary, increasing MSME credit access by 35%, despite challenges such as inconsistencies in BPN-Kemenkumham registration, over-collateralisation, and crypto regulatory gaps triggering priority overlaps and bankruptcy disputes. Reforms via the National Collateral Registry (RUU Cipta Kerja 2.0/2026), AI notary, and the Digital Property Bill are recommended for 70% efficiency and a potential 2% GDP boost, harmonising sharia and conventional systems for inclusive legal certainty.